RURAL COMMUNITY UNDERSTANDING OF THE BENEFITS OF HEALTH INSURANCE IN INDONESIA: LITERATURE REVIEW - Safira, Meylia; Nurdin, Ambia (Aceh Sanitation Journal, 2023)
The knowledge of rural communities regarding health insurance is still limited, leading them to use insurance less compared to urban residents. This lack of understanding is related to the characteristics of rural communities, which are heavily influenced by religious factors in their perception of insurance laws. This study aims to analyze and understand effective and efficient methods of socialization to reach all groups and layers of society. The study is a literature review that cites several online sources such as Google Scholar and Garuda, using keywords such as "Understanding Rural Communities," "Health Insurance," and "Insurance Benefits." The inclusion criteria used focus on the understanding of rural communities regarding the benefits of health insurance. The research findings indicate that the understanding of insurance among the community varies, where some rural communities have grasped it, but many are still unaware of the importance of health insurance benefits. This is influenced by factors such as individual characteristics, the surrounding environment, and limited access to healthcare services. Therefore, there is a need for increased education and socialization among rural communities regarding the benefits of health insurance in order to improve public health.